Improving Student Learning Independence by Applying the Peer-Tutoring Method in Basic Programming Subjects for Vocational High School - Joko Laksono (Jurnal Guru Komputer, 2021)
Learning method is a method or effort made by the process of educators so that the teaching and learning process of student is achieved in accordance with the objectives. This learning method is very important to do so that the teaching and learning process is fun and does not make the students too tired, and the student can easily grasp the knowledge of the educators. One learning method that can be used to improve student abilities is using the peer tutoring method. The peer tutoring method is a learning pattern in which a person or several clever students are appointed by the teacher to provide learning assistance for students who are less intelligent. In this study, using the peer tutoring method in basic programing subject was proven to increase the independence of student.